Analisis Maksimalisasi Utilitas Konsumen Melalui Grafik dan Persamaan Rumus - Siti Masytoh Diyandini; Eti Kurniati; Onoy Rohaeni (Bandung Conference Series: Mathematics, 2024)
Abstract. This research explores how to maximize consumer utility within the constraints of a budget through the analysis of two goods and n-goods using graphs and equations. The basic assumption is that consumers have income allocated between two goods (x and y) with their respective prices. Through discussions on budget constraints, marginal substitution, and indifference curves, it is concluded that maximum utility is achieved when the entire income is spent with the marginal substitution rate (MRS) equal to the price ratio of the goods. Explanations are provided for situations where consumers can achieve maximum utility without consuming one of the goods, depending on individual preferences. The importance of optimal income allocation is also revealed in the mathematical analysis and Lagrange Multiplier Equation for n-goods cases. The condition equations indicate that the price of goods must be proportional to their marginal value for optimal purchases to occur. The research findings emphasize the significance of distributing additional benefits from each extra income uniformly across all consumed goods. This study makes a significant contribution to understanding the fundamentals of consumer economic behavior and establishes a theoretical foundation for further analysis in this field. Research steps involve information collection, mathematical analysis, and understanding economic concepts, with anticipated outcomes providing in-depth insights and meaningful contributions to understanding consumer expenditure allocation decisions. Abstrak. Penelitian ini membahas cara memaksimalkan utilitas konsumen dalam konteks keterbatasan anggaran melalui analisis dua barang dan n-barang menggunakan grafik dan persamaan. Asumsi dasar adalah konsumen memiliki pendapatan yang dialokasikan antara dua barang (x dan y) dengan harga masing-masing. Melalui pembahasan tentang budget constraint, substitusi marjinal, dan kurva indifferen, disimpulkan bahwa utilitas maksimal tercapai saat seluruh pendapatan dihabiskan dengan tingkat substitusi marjinal (MRS) sama dengan rasio harga barang. Penjelasan diberikan untuk situasi di mana konsumen dapat mencapai utilitas maksimal tanpa mengonsumsi salah satu barang, tergantung pada preferensi individu. Pentingnya alokasi pendapatan optimal juga terungkap dalam analisis matematis dan Persamaan Lagrange Multiplier untuk kasus n-barang. Persamaan kondisi menunjukkan bahwa harga barang harus proporsional dengan nilai marginalnya agar pembelian optimal terjadi. Hasil penelitian menggarisbawahi pentingnya meratakan manfaat tambahan dari setiap pendapatan tambahan ke semua barang yang dikonsumsi. Penelitian ini memberikan kontribusi signifikan dalam memahami dasar-dasar ekonomi perilaku konsumen dan menciptakan landasan teoritis untuk analisis lebih lanjut di bidang ini. Langkah-langkah penelitian melibatkan pengumpulan informasi, analisis matematis, dan pemahaman konsep-konsep ekonomi, dengan hasil yang diharapkan memberikan wawasan mendalam dan kontribusi berarti untuk pemahaman keputusan alokasi pengeluaran konsumen.